PERFORMANCE AND EFFICIENCY OF GLASS AND CARBON FIBER BARS FOR SELF-PROPELLED SPRAYERS - Albernaz, Danilo Fernandes; Ferraz-Almeida, Risely (ENERGIA NA AGRICULTURA, 2020)
PERFORMANCE AND EFFICIENCY OF GLASS AND CARBON FIBER BARS FOR SELF-PROPELLED SPRAYERS DANILO FERNANDES ALBERNAZ1, RISELY FERRAZ-ALMEIDA1 1Luiz de Queiros College of Agriculture, Departament of Soil Sciente, University of São Paulo, Avenida Pauda Dias, 11, 13418-900, Piracicaba, São Paulo, Brazil, albernazdanilof@hotmail.com; rizely@gmail.com ABSTRACT: Agribusiness has a fundamental role in the Brazilian economy, responsible for stimulating the Gross Domestic Product, creating investment and development opportunities. High yields have been faced in pest-free areas in different crop regions. However, pest control with high efficiency is a challenge for many farmers. In this context, self-propelled sprayers with a high efficiency are necessary to increase the quality and speed of application with a direct decreasing equipment’s operational cost. This work aims: (i) present the advantages of using carbon fiber booms in the performance of self-propelled sprayers; (ii) compare weight and fuel consumption of self-propelled sprayers with carbon fiber booms and conventional carbon steel booms. The results showed that the self-propelled sprayers with glass/carbon fiber boom presented better application performances, considered 6% more productive, 1.8% lighter, and 44% more economical in fuel consumption than the conventional carbon steel boom. Based on the results, the self-propelled glass/carbon fiber boom is a better alternative to increase agricultural spraying productivity. Keywords: efficiency of the application, carbon fiber, composite, fuel consumption. DESEMPENHO E EFICIÊNCIA DE BARRAS DE VIDRO E FIBRA DE CARBONO PARA PULVERIZADORES AUTO-PROPELIDO RESUMO: O agronegócio tem papel fundamental na economia brasileira com significante participação no Produto Interno Bruto, criando oportunidades de investimento e desenvolvimento no Brasil. Em todas as culturas, altas produtividades estão associadas a áreas livres de pragas, no entanto, o controle de pragas é um desafio para muitos agricultores. Nesse contexto, a escolha de pulverizadores eficientes para aplicação de pesticidas torna-se uma necessidade para aumentar a qualidade e velocidade da aplicação, e diminuir o custo operacional deste equipamento. Este trabalho tem como objetivos: (i) apresentar as vantagens do uso de barras de fibra de carbono no desempenho de pulverizadores; (ii) comparar o peso e o consumo de combustível de pulverizadores com barras de fibra de carbono, e pulverizadores com barras convencionais de aço carbono. Os resultados mostraram que os pulverizadores com barra de fibra de vidro/carbono apresentaram melhores desempenhos de aplicação, considerado 6% mais produtivo, 1,8% mais leve, e 44% mais econômico em consumo de combustível em comparação com a barra de aço carbono convencional. Portanto, pode-se concluir que para otimizar a pulverização de culturas agrícolas, a barra de fibra de vidro/carbono é uma alternativa mais eficiente para aumentar a produtividade na pulverização agrícola. Palavras-chaves: eficiência de aplicação, fibra de carbono, composto, consumo de combustível.